(untitled) (Лучшие интеллектуальные исследования, 2025)
This article explores the tense system in English, their structures, and contextual usage, along with the differences among various tenses. It analyzes the most common grammatical mistakes made by learners and identifies the underlying causes. The article presents both theoretical explanations and practical examples, supported by statistical data and expert opinions.